Disciplines and ideas in the applied social sciences - Sampa, Elias M. (Sampaloc Manila : Rex Book Store, Inc., 2019)
"This textbook introduces students to the disciplines and ideas that form part of applied social sciences by drawing on the theories and principles of psychology, sociology, anthropology, and other social sciences. The coverage of applied social sciences centers on social science, counseling, social work, and communication, which are seamlessly threaded together. This book focuses on the processes and applications of these applied disciplines in critical development areas. It aims to empower students to develop competencies in interacting and relating with other individuals, groups, and communities; to apply social science principles, practices, and tools in addressing several appropriate development areas; and to sharpen their analytical skills specific to the processes and life context where these applied disciplines are at work".
Includes references and index.
English text.
Keywords: Social sciences; Social sciences -- Study and teaching